Peran guru dalam evalusi ranah psikomotorik pasca pandemi pada mata pelajaran pendidikan agama Islam di SMK Batik 1 Surakarta - Mega Paramitha; Nurul Latifatul Inayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
The use of information technology during the pandemic is one step to face the industrial revolution 4.0 in the field of education. The industrial revolution 4.0 in the world of education means that all components in education are able to integrate the use of both physical and non-physical technology in learning. This is also continuously being developed by the Batik 1 Surakarta Vocational School in carrying out the learning process from the beginning to the evaluation stage. The evaluation process occupies an important position in the learning process, because evaluation can influence learning. So that the evaluation process requires the role of teachers who have supporting competencies who can design evaluations appropriately, accurately, and transparently. This research is qualitative research with a descriptive study approach. The aim of this research is to determine the role of teachers in evaluating the psychomotor domain after the pandemic. Data collection is done by means of observation, interviews, and documentation. The collected data was then analyzed using the Miles and Hubermen model data analysis techniques. From the data analysis, it was found that the role of the teacher in the post-pandemic psychomotor domain evaluation process starts from the evaluation planning teacher to the teacher reporting the results of the evaluation as part of conveying information about student competencies and making improvements to the quality of learning and school facilities.